A giant ureteral fibroepithelial polyp in a middle-aged woman: A case report (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Fibroepithelial polyp, especially in the ureter, is a rare condition to report. Though it is a benign tumour, patients usually present with haematuria, which mimics the symptoms of upper urinary tract urothelial cell carcinoma.Case description and management: We present a case of a 45-year-old woman with painless episodic haematuria for 1 month. Urethrocystoscopy and ureteroscopy detected a pedunculated, long, narrow polyp (6 cm) arising from the mid ureter. It was resected by cutting the base of the polyp with a cold cup biopsy forceps. Haematuria resolved following the procedure, and the patient’s recovery was uneventful. A fibroepithelial polyp of the ureter is a rare benign tumour that mimics the typical findings of upper urinary tract urothelial cell carcinoma. Therefore, it should be included in the differential diagnosis of upper urinary tract urothelial cell carcinoma. Diagnosis can be made with careful history-taking and imaging techniques.Conclusion: A ureteral fibroepithelial polyp can be safely managed with endoscopic resection.